Navigating post-pandemic challenges for school teachers in a South Indian city - Sophia, M.; Sebastine, A. Anand Jerard (Edelweiss Applied Science and Technology, 2025)
World Health Organization (WHO) published its first report regarding the COVID-19 pandemic in the year 2020; a heavy disaster was experienced throughout the globe. The unforeseen pandemic due to COVID-19 has influenced the lives of many people. This study examines the challenges teachers in Thanjavur, a South Indian city, face when navigating post-pandemic schools. Using simple random sampling, the study was conducted on 110 school teachers in the Thanjavur District. The DASS-42 scale developed by Lovibond and Lovibond (1995) was employed to collect data. A sudden transformation in the teaching-learning process from “offline to online (during COVID-19) and online to offline” has created serious implications on the psychosocial aspects among school teachers in terms of experiencing mild to extremely severe stress (33.6%), mild to extremely severe anxiety (57.4%), and mild to extremely severe depressive-like symptoms (47.4%). Therefore, the study revealed psychosocial implications on instructors’ performance during COVID-19 periods. Educational stakeholders can develop more effective strategies to promote the psychological resilience of teachers and ensure their overall well-being amid challenging circumstances such as the post-COVID-19 pandemic. The conclusion of the study highlights the significant impact of the pandemic on the mental health of teachers, with significant associations between job status, education level, and years of experience with anxiety and stress levels.